Effects of large horizontal winds on the equatorial electrojet - Hysell, D. L. (2002)
The effects of large winds on the low-latitude E region ionosphere and the equatorial electrojet in particular are analyzed theoretically, computationally, and experimentally. The principles that govern the relationship between electric fields, currents, and winds in steady flows in the ionosphere are reviewed formally. A three-dimensional numerical model of low-latitude ionospheric electrostatic potential is then described. Scaled wind profiles generated by the National Center for Atmospheric Research (NCAR) thermosphere/ionosphere/mesosphere electrodynamics general circulation model (TIME-GCM) are used as inputs for the potential model. The model shows that the horizontal wind component drastically modifies the vertical polarization electric field in the electrojet and drives strong zonal and meridional currents at higher dip latitudes outside the electrojet region. Comparison between the model output and coherent scatter radar observations of plasma irregularities in the electrojet indicate that strong winds and wind shears are present in the E region over Jicamarca that are roughly consistent with NCAR model wind predictions if the amplitudes of the latter are increased by about 50%.